A MODEL OF SUCCESS FACTORS FOR COMMUNITY INNOVATION NETWORKS TOWARD SUSTAINABILITY IN CHIANG MAI PROVINCE - Gerdruang, Atiporn (Journal of MCU Nakhondhat, 2025)
This research aimed to: 1) Examine the factors of innovation networks for community development, 2) Investigate the success of community innovation networks, 3) Analyze the factors influencing the success of these networks, and 4) Develop a model of success factors for sustainable community innovation networks. Quantitative research design was employed. The sample consisted of 580 respondents, including community leaders, local administrative organizations, educational institutions, and private-sector representatives in Chiang Mai Province, selected through stratified random sampling. A questionnaire was used as the main data collection tool. Data were analyzed using mean, standard deviation, and multiple regression analysis. The findings revealed that: 1) The key factors of innovation networks for community development consist of four major components participation, knowledge integration, resource support, monitoring and evaluation. Overall, these factors were rated at a high level, with participation being the most significant component. 2) The success of community innovation networks resulted from the collaborative efforts of multiple sectors government, private sector, education, and community members leading to substantial progress in economic, social, cultural, and environmental dimensions. 3) Multiple regression analysis indicated that all four factors had a statistically significant influence on network success at the .01 level and collectively explained 86.5% of the variance in success, with participation exerting the strongest influence. 4) The results supported the development of a model of success factors for sustainable community innovation networks, which can serve as both a policy and practical framework for enhancing participation, optimizing resource management, and improving transparency in monitoring and evaluation systems.